1978
DOI: 10.1083/jcb.79.2.444
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and localization of myosin in the brush border of intestinal epithelial cells

Abstract: The brush border of intestinal epithelial cells consists of a tightly packed array of microvilli, each of which contains a core of actin filaments. It has been postulated that microvillar movements are mediated by myosin interactions in the terminal web with the basal ends of these actin cores (Mooseker, M. S. 1976. J. Cell Biol. 71:417-433). We report here that two predictions of this model are correct: (a) The brush border contains myosin, and (b) myosin is located in the terminal web. Myosin is isolated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
79
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 30 publications
(30 reference statements)
8
79
0
Order By: Relevance
“…Brush Border Isolation : Brush borders were isolated from intestinal epithelium of chickens according to the method of Mooseker et al (31) using modifications described in Keller and Mooseker (37). In this method, brush borders, once isolated by homogenization of epithelial cells in low ionic strength medium containing divalent cation chelators, are transferred to a buffer termed brush border stabilization solution (BBSB) containing 75 mM KCI, 5 .0 mM MgSO,, 1 .0 mM EGTA, 0 .2 mM dithiothreitrol .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brush Border Isolation : Brush borders were isolated from intestinal epithelium of chickens according to the method of Mooseker et al (31) using modifications described in Keller and Mooseker (37). In this method, brush borders, once isolated by homogenization of epithelial cells in low ionic strength medium containing divalent cation chelators, are transferred to a buffer termed brush border stabilization solution (BBSB) containing 75 mM KCI, 5 .0 mM MgSO,, 1 .0 mM EGTA, 0 .2 mM dithiothreitrol .…”
Section: Methodsmentioning
confidence: 99%
“…Electron microscopy-immunolocalization studies using antibodies to either TW 260/240 (29) or brain fodrin (30) indicate that TW 260/240 (or its equivalent in mammalian brush borders) comprises at least one type of "interdigitating" filaments that cross-link core rootlets. A second class of cross-linking filaments that appear to be greater in diameter than the TW 260/240 filaments when visualized by the quick-freeze, deep-etch rotary replication (QFDERR)' technique (27) may be comprised ofbrush border myosin that, like TW 260/240, is localized exclusively in the terminal web (31)(32)(33)(34). The studies of Hirokawa et al .…”
mentioning
confidence: 99%
“…Light and EM immunocytochemical studies to date (2,7,9,18) have shown that the apices of intestinal cells contain the essential contractile proteins, including actin, myosin, tropomyosin, and a-actinin . EM has not revealed how all these proteins could fit together to provide rigid support and flexible contractility in an appropriate manner .…”
Section: The Cytoskeleton Of Intestinal Cellsmentioning
confidence: 99%
“…A large number of biochemical and immunocytochemical studies have focused on this region of the intestinal cell . These studies have defined the proteins that are present in the terminal web, but they have THE JOURNAL OF CELL BIOLOGY " VOLUME 91 NOVEMBER 1981 399-409 © The Rockefeller University Press -0021-9525/81/11/399/11 $1 .00not been able to demonstrate exactly how these proteins are put together (2,3,4,(6)(7)(8)(9)18) . The micrographs presented here display certain advantages over traditional transmission electron micrographs of plastic-embedded and sectioned material, and thus help to reveal how the terminal web is organized.…”
mentioning
confidence: 99%
See 1 more Smart Citation